Hyperprogressive disease in patients suffering from solid malignancies treated by immune checkpoint inhibitors: A systematic review and meta-analysis - Zijun Zhao; Jin Bian; Junwei Zhang; Ting Zhang; Xin Lu (Frontiers in Oncology, 2022)
IntroductionHyperprogressive disease (HPD) is a paradoxically rapid disease progression during or shortly after antitumor treatment, especially immune checkpoint inhibitors (ICIs). Various diagnosis criteria of HPD cause heterogeneous incidence rates in different clinical research, and there is no consensus on potential risk factors associated with HPD occurrence. Hence, we aimed to summarize incidence of HPD in ICI treatment for solid tumors. Clinicopathological factors associated with HPD are also analyzed.MethodsClinical studies about HPD during/after ICI treatment of solid malignancies are included. Pubmed, Embase, and Cochrane library were searched for eligible studies published before October 7. The Newcastle–Ottawa scale was used to assess the quality of the included studies. Random effect and fixed effect models were, respectively, used for pooling incidence of HPD and analysis of risk factors for HPD. Heterogeneity, subgroup analysis, and publication bias were also analyzed. All meta-analysis was performed via R software (y -40v4.0.2).ResultsForty-one studies with 6009 patients were included. The pooled incidence of HPD was 13.2% (95% CI, 11.2%–15.4%). Head and neck cancer (HNC) had the highest incidence of HPD (18.06%), and melanoma had the lowest (9.9%). Tumor types (P = .0248) and gender ratio (P = .0116) are sources of heterogeneity of pooled incidence of HPD. For five clinicopathological factors associated with HPD, only programmed cell death protein 1 ligand 1 (PD-L1) positivity was a preventive factor (odds ratio = 0.61, P <.05). High lactate dehydrogenase (LDH) level (OR = 1.51, P = .01), metastatic sites >2 (OR = 2.38, P <.0001), Eastern Cooperative Oncology Group Performance Score ≥2 (OR = 1.47, P = .02), and liver metastasis (OR = 3.06, P <.0001) indicate higher risk of HPD.ConclusionsThe pooled incidence of HPD was less than 15%, and HNC had the highest incidence of HPD. LDH and PD-L1 are remarkable biomarkers for prediction of HPD in future medical practice.